2018
DOI: 10.1175/jcli-d-17-0379.1
|View full text |Cite
|
Sign up to set email alerts
|

Sea Surface Temperature in the Subtropical Pacific Boosted the 2015 El Niño and Hindered the 2016 La Niña

Abstract: After the quick decaying of the 2015 super El Niño, the predicted La Niña unexpectedly failed to materialize to the anticipated standard in 2016. Diagnostic analyses, as well as numerical experiments, showed that this ENSO evolution of the 2015 super El Niño and the hindered 2016 La Niña may be essentially caused by sea surface temperature anomalies (SSTAs) in the subtropical Pacific. The self-sustaining SSTAs in the subtropical Pacific tend to weaken the trade winds during boreal spring–summer, leading to ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The cold SSTAs in the SEP region contributed to the anomalous easterly winds in the eastern equatorial Pacific, which suppressed the equatorial SST warming. Meanwhile, following the wind-evaporation-SST feedback, the cold SSTAs in the SEP could sustain themselves and penetrate into the equatorial Pacific (Min et al, 2015(Min et al, , 2017Su et al, 2018). The SSTAs in the SEP region can favor SSTAs development in the equatorial eastern Pacific and may lead to different flavors of El Niño (Min et al, 2017;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The cold SSTAs in the SEP region contributed to the anomalous easterly winds in the eastern equatorial Pacific, which suppressed the equatorial SST warming. Meanwhile, following the wind-evaporation-SST feedback, the cold SSTAs in the SEP could sustain themselves and penetrate into the equatorial Pacific (Min et al, 2015(Min et al, , 2017Su et al, 2018). The SSTAs in the SEP region can favor SSTAs development in the equatorial eastern Pacific and may lead to different flavors of El Niño (Min et al, 2017;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since the ENSO turned out to be an El Niño event after the summer of 2006 (figures S9 and S10), one may speculate that the present 2017/18 La Niña status could continue to decay during the following summer and could perhaps develop into a warming phase of the ENSO pendulum. However, several key factors can influence the ENSO formation, such as westerly wind bursts , Lian et al 2017 and subtropical Pacific SSTAs (Su et al 2018) in the late spring and early summer seasons. Hence, the final evolution of the present 2017/18 La Niña status in the future presents many uncertainties.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Perhaps the most interesting application of the ENSO pendulum is associated with the evolution of the 2014-2015 El Niño (figures 4(e)-(f); figures S11-S13). The development of an anticipated strong El Niño event was hindered in the boreal summer of 2014 (Menkes et al 2014, Min et al 2015, Hu and Fedorov 2016, Su et al 2018. The SSTAs in the Niño-3 region warmed up to above 0.5 • C, the SSTAs in the Niño-3.4 were approximately 0.5 • C after May 2014, and the ENSO pendulum turned anticlockwise from its former phase of C7-C10 in May 2014 (figure 4(e); figure S11).…”
Section: Enso Pendulum Of the 2014-2015 El Niñomentioning
confidence: 99%
See 1 more Smart Citation
“…A number of papers have examined various aspects of the nature, characteristics and dynamical processes thought to underlie the 2014–2016 El Niño. Some, such as Menkes et al (2014), Min et al (2015), Hartmann (2015) and Maeda et al (2016), have focused on various potential causes of its development in 2014, others such as Lian et al (2017), Santoso et al (2017), Hu and Fedorov (2017) and Su et al (2018) have focused on its strong 2015–2016 signature, while Zhu et al (2016), L’Heureux et al (2017), Ineson et al (2018) and Santoso et al (2019) examined how well it was predicted. Peng et al (2018) examined this El Niño in terms of its influence on the Pacific and North American boreal winter of 2014–2015 and suggested that it was indicative of the operation of the North Pacific Mode (NPM) rather than ENSO.…”
Section: Insights Into the 2014–2016 Protracted El Niñomentioning
confidence: 99%